1998
DOI: 10.1038/bjc.1998.586
|View full text |Cite
|
Sign up to set email alerts
|

Tumour hypoxia and vascular density as predictors of metastasis in squamous cell carcinoma of the uterine cervix

Abstract: Summary Some clinical studies involving several histological types of cancer have suggested that high vascular density in the primary tumour promotes metastasis. Other studies have suggested that a high incidence of metastases is associated with low oxygen tension in the primary tumour. The purpose of the study reported here was to search for correlations between incidence of metastases and oxygen tension or vascular density in the same population of patients. Thirty-eight consecutive patients with squamous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
106
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 32 publications
7
106
1
2
Order By: Relevance
“…To facilitate tumor cell detachment, migration and invasion, hypoxia can down-regulate cell adhesion molecules such as integrins (Hasan et al, 1998), and upregulate the urokinase-type plasminogen activator receptor (uPAR; Rofstad et al, 2002) and the autocrine motility factor (AMF; Niizeki et al, 2002). An association between primary tumor oxygenation and the likelihood of distant metastasis has been reported in clinical studies involving patients with high-grade soft tissue sarcoma (Brizel et al, 1996) and advanced squamous cell carcinoma of the uterine cervix (Sundfor et al, 1998;Pitson et al, 2001;Fyles et al, 2002). Also, a positive correlation has been observed between tumor lactate concentration and the presence of metastatic deposits in cervix and head and neck squamous cell carcinomas (Rofstad, 2000;Brizel et al, 2001), while ATP and glucose concentration did not show significant correlation (Rofstad, 2000).…”
Section: Molecular Effectsmentioning
confidence: 77%
See 2 more Smart Citations
“…To facilitate tumor cell detachment, migration and invasion, hypoxia can down-regulate cell adhesion molecules such as integrins (Hasan et al, 1998), and upregulate the urokinase-type plasminogen activator receptor (uPAR; Rofstad et al, 2002) and the autocrine motility factor (AMF; Niizeki et al, 2002). An association between primary tumor oxygenation and the likelihood of distant metastasis has been reported in clinical studies involving patients with high-grade soft tissue sarcoma (Brizel et al, 1996) and advanced squamous cell carcinoma of the uterine cervix (Sundfor et al, 1998;Pitson et al, 2001;Fyles et al, 2002). Also, a positive correlation has been observed between tumor lactate concentration and the presence of metastatic deposits in cervix and head and neck squamous cell carcinomas (Rofstad, 2000;Brizel et al, 2001), while ATP and glucose concentration did not show significant correlation (Rofstad, 2000).…”
Section: Molecular Effectsmentioning
confidence: 77%
“…Hypoxia-driven cellular modifications may contribute to this poor prognostic outlook, giving rise to more aggressive locoregional disease, invasive capacity, and angiogenesis ( Fig. 1; Brizel et al, 1996;Sundfor et al, 1998;Graham et al, 1999;Hockel et al, 1999;Walenta et al, 2000).…”
Section: Hypoxia and Response To Treatment Radioresistancementioning
confidence: 99%
See 1 more Smart Citation
“…Presently, the determination of oxygen concentration with polarographic electrodes is the only method of measuring hypoxia that has been extensively studied in patients. Decreased tumour oxygenation, as measured with polarographic electrodes, has been reported to be a predictor of poor local response following radiotherapy in cervix cancer (Höckel et al, 1993;Fyles et al, 1998;Sundfør et al, 1998;Knocke et al, 1999;Lyng et al, 2000) head and neck cancer (Gatenby et al, 1988;Nordsmark et al, 1996;Brizel et al, 1997) and soft tissue sarcoma (Brizel et al, 1996). Recently, clinical data have emerged suggesting that hypoxia adversely affects locoregional control of cervical cancer, irrespective whether the initial treatment modality is radiotherapy or surgery (Höckel et al, 1996).…”
mentioning
confidence: 99%
“…Several studies of advanced cervix carcinoma have demonstrated a positive association between poor outcome of radiation therapy and poor oxygenation of the primary tumour, measured with the Eppendorf pO 2 histograph prior to treatment (Höckel et al, 1993;Fyles et al, 1998a;1998b). The worse treatment outcome of the patients with the most hypoxic tumours could be related to the classical oxygen effect (Bush, 1986;Overgaard et al, 1989) or to the development of metastases associated with hypoxia (Höckel et al, 1996;Sundfør et al, 1998).…”
mentioning
confidence: 99%